Critical Evaluation of the Partial Revision of Law Number 13 of 2003 on Labour in the Job Creation Law - Novrian, Jimmi; Yusuf, Rizki Fauzan (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2024)
The stages of the procedure for the formation of laws and regulations in Indonesia have been regulated in Law Number 12 of 2011 on the Formation of Laws and Regulations. In Indonesia there are three methods in the preparation or regulation of regulations in Indonesia, namely codification, unification, and modification. Modification of the labour cluster in the Job Creation Law has attracted public attention. This study critically evaluates how partial revisions are applied to Law Number 13 of 2003 on Labour through the omnibus law method in the Job Creation Law. The research method is normative legal research and prescriptive research with data source taken from primary legal materials and secondary legal materials. The result shows that there are quite a lot of forms of changes related to the Labour Law. It can be concluded that overall there are 72 articles from 7 chapters and 4 sections of changes to Law Number 13 of 2003 in Law Number 11 of 2020. The partial revision modifies the legal politics of labour law which was originally for the protection of workers into legal politics that benefit employers or investors.